2014
DOI: 10.3390/rs6087783
|View full text |Cite
|
Sign up to set email alerts
|

Salt Content Distribution and Paleoclimatic Significance of the Lop Nur “Ear” Feature: Results from Analysis of EO-1 Hyperion Imagery

Abstract: Lop Nur, a playa lake located on the eastern margin of Tarim Basin in northwestern China, is famous for the "Ear" feature of its salt crust, which appears in remote-sensing images. In this study, partial least squares (PLS) regression was used to estimated Lop Nur playa salt-crust properties, including total salt, Ca , and Fe 2+ using laboratory hyperspectral data. PLS results for laboratory-measured spectra were compared with those for resampled laboratory spectra with the same spectral resolution as Hyperion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Despite these factors, the RPD was 2.21, which still indicates the adequacy of the predictive ability of the PLSR model. The reduction in model performance with the scaling up of observations from laboratory to satellite was also observed by Zhang et al [27], after modeling Ca 2+ using Hyperion/EO-1 data in a land degradation area in China. They highlighted the poor SNR of Hyperion as one of the factors that affected the quality of the estimates.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Despite these factors, the RPD was 2.21, which still indicates the adequacy of the predictive ability of the PLSR model. The reduction in model performance with the scaling up of observations from laboratory to satellite was also observed by Zhang et al [27], after modeling Ca 2+ using Hyperion/EO-1 data in a land degradation area in China. They highlighted the poor SNR of Hyperion as one of the factors that affected the quality of the estimates.…”
Section: Discussionsupporting
confidence: 63%
“…Such correlation is not observed for all the salts and is typical of the predominance of NaCl. For instance, when treating the soils of the study area with increasing levels of salinization in the laboratory, Moreira et al [27] observed an increase in brightness for NaCl and a decrease in brightness for MgCl 2 and CaCl 2 with increased salt concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the visible, near infrared, or short-wave infrared spectral bands from the optical sensors to be promising for the detection of surface soil salinity [11][12][13][14][15]. In addition, hyperspectral data have been successfully used in several studies on soil salinity, enabling quantitative assessment of salt-affected soils [16][17][18][19][20][21][22]. However, practical limitations associated with hyperspectral imagery, including the availability of orbital data and the limited spatial coverage of the existing satellite sensors, still limit its potential for regional monitoring of salt-affected soils [23].…”
Section: Introductionmentioning
confidence: 99%
“…Though Hyperion images are characterized by relatively high levels of noise [59,[62][63][64][65][66][67][68], they represent important alternatives to datasets generated by orbiting multispectral systems. In numerous case studies, Hyperion images have proven useful in the mapping of lithological and mineralogical classes [63,64,67,[69][70][71][72][73][74][75][76]. In the Sudbury region, Hyperion images have previously been used in the study of vegetation growth related to land reclamation near smelters [20,77].…”
Section: Hyperion Imagesmentioning
confidence: 99%